2020
DOI: 10.5860/crl.81.4.662
|View full text |Cite
|
Sign up to set email alerts
|

The Gender Wage Gap in Research Libraries

Abstract: The gender wage gap impacts millions of women throughout the US and world, with women in the US making on average 82 percent of men's salaries (US Census Bureau, 2018). In research libraries, a field dominated by women, this has historically been true as well, with men rising to top positions at a higher rate and making more money than women in the same positions. Over the decades following the implementation of Affirmative Action, the number of women in administrative positions in research libraries has incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…But we should also think about the potential impact of these uses of AI on equality, diversity and inclusion within a profession which has a female majority but still has persistent gender pay gap (Hall et al, 2016; Howard et al, 2020). AI should not be seen simplistically as a neutral technology.…”
Section: Discussion: How Will Ai Impact Employment and Equality Diver...mentioning
confidence: 99%
“…But we should also think about the potential impact of these uses of AI on equality, diversity and inclusion within a profession which has a female majority but still has persistent gender pay gap (Hall et al, 2016; Howard et al, 2020). AI should not be seen simplistically as a neutral technology.…”
Section: Discussion: How Will Ai Impact Employment and Equality Diver...mentioning
confidence: 99%
“…One way to acknowledge and appreciate this work is through its compensation. Despite the fact that, in at least one study, researchers found "higher incidences of burnout among female respondents, particularly those between ages 35 and 44," (Dixon, 2022), there is also data to support that "males at every level [of the academic library] make significantly more, both statistically and in terms of lost wages during the course of a career, than their female colleagues" (Howard et al, 2020). This mismatch of work and compensation would suggest that social-emotional labor, and care work in general, is not formally compensated as work.…”
Section: Social-emotional Labor Gender and Experiencementioning
confidence: 99%
“…2 According to Howard, Habashi, and Reed (2020), librarianship today in the United States has become "a female-dominated profession, with about one man for every five women" (664).…”
Section: Notesmentioning
confidence: 99%